2017
DOI: 10.1371/journal.pone.0188115
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation in open vs. minimally invasive dorsal stabilization of thoracolumbar fractures

Abstract: Standard open and percutaneous minimally invasive surgical procedures co-exist in the treatment of fractures of the thoracolumbar spine. Shorter skin incisions just above the pedicles are used in minimally invasive procedures. Full-length skin incisions and invasive preparations are applied in the standard open approach. While both methods show equivalent rates of intraoperative surgical complications and comparable clinical and radiological outcomes, blood loss and operation time have shown to be decreased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Ganse et al showed that, in proximal femur fractures, the surgery itself alters skin and subcutaneous microcirculation around the greater trochanter throughout the postoperative period, compared to the healthy leg. The same was previously demonstrated for calcaneal and thoracolumbar fractures, where microcirculation, in a minimally invasive approach, was compared to standard open fixation [17,18]. It is a common observation that microcirculation is altered after trauma [15,19].…”
Section: Discussionmentioning
confidence: 65%
“…Ganse et al showed that, in proximal femur fractures, the surgery itself alters skin and subcutaneous microcirculation around the greater trochanter throughout the postoperative period, compared to the healthy leg. The same was previously demonstrated for calcaneal and thoracolumbar fractures, where microcirculation, in a minimally invasive approach, was compared to standard open fixation [17,18]. It is a common observation that microcirculation is altered after trauma [15,19].…”
Section: Discussionmentioning
confidence: 65%
“…The O2C device as a tool for noninvasive detection of hemoglobin saturation and blood flow using laser Doppler technique and white light spectroscopy allows for valid and reproducible quantitative determination of microcirculatory parameters [ 19 24 ], as well as identification of possible influencing factors in healthy subjects [ 23 , 25 ]. Currently, O2C studies have provided evidence for altered soft tissue microcirculation after peripheral artery occlusive disease [ 26 ] as well as for individual healing tendencies depending on the microcirculatory parameters in patients with burns [ 27 , 28 ] and chronic diabetic foot ulcers [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, O2C studies have provided evidence for altered soft tissue microcirculation after peripheral artery occlusive disease [ 26 ] as well as for individual healing tendencies depending on the microcirculatory parameters in patients with burns [ 27 , 28 ] and chronic diabetic foot ulcers [ 19 ]. In this context, recent data in the treatment of fractures of the thoracolumbar spine indicated differences in microcirculation between open and minimally invasive approaches [ 24 ]. High oxygen saturation and high blood flow values clearly contribute to a good prognosis of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective, multi-institutional study on lumbar spine surgery in morbidly obese patients, improvement in back and leg pain, physical component score/mental component score, and life quality was observed with no divergence in post-operative complications between MIS-TLIF and open TLIF [ 59 ]. While in the other study, compared to open TLIF, MIS-TLIF improved blood flow in the incised skin with no change in levels of blood oxygen and hemoglobin [ 60 ]. In a long-term clinical follow-up for treatment of one-segment lumbar disc herniation, MIS-TLIF predominated conventional TLIF in efficaciously reduced blood loss, intramuscular pressure, operative time, mean return to work time, as well as visual analogue score (VAS) and ODI indices, implying pain relief [ 61 ].…”
Section: Mis–tlif: the Surgical Proceduresmentioning
confidence: 99%